Stimulating National Economic Growth Through Synergy of Digital Innovation and Green Economy - Zulfa, Fatasya Aulya Ngindana; Putri, Bunga Andiya; Permatasari, Ditya (Formosa Journal of Sustainable Research, 2024)
This study aims to analyze the influence of digital innovation and green economy on Indonesia's national economic growth. By adopting a quantitative approach and descriptive design, this study uses secondary data from the period 2019-2023 obtained from various official sources. The digital innovation variable is proxied by indicators such as e-commerce usage and digital transactions, while the green economy is measured through environmental indicators such as forest area and emission reduction. Economic growth is represented by GDP, per capita income, and unemployment rate. Multiple linear regression analysis shows that digital innovation has a significant positive effect on economic growth, while the green economy has a significant negative effect. Simultaneously, both independent variables have a significant effect on economic growth. These findings highlight the important role of digital innovation in driving economic growth and underline the short-term challenges in implementing a green economy. This study provides valuable insights for policymakers in designing sustainable economic development strategies, considering the synergy between technological advances and environmental sustainability principles